KEPUTUSAN INDONESIA MELAKUKAN KERJASAMA PEMBELIAN PESAWAT TEMPUR SUKHOI 35 DENGAN RUSIA TAHUN 2015-2018 - Novria "; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to explain the general conditions of Indonesian defense equipment until 2014, to find out the reasons Indonesia chose Russia in purchase cooperation for fighter flight in 2015, and systematically analyze Indonesia and Russia in purchase cooperation of  Su-35 fighter flight in 2015-2018.The research using Neorealism perspective, which nation-state as the level of analysis. Theory of national security and the concept of national interest are using to examine the problem. Using qualitative methods through library research to achieve goals, derived from data obtained from journals, official documents, mini-thesis, books, and the internet to analyze Indonesia's decision to purchase Sukhoi 35 fighter flight with Russia year of  2015 until 2018.This research proves that Indonesia chose Russia for Su-35 fighter flight purchase cooperation in 2015 is due to efficiency and pragmatic reasons, which is Russia seen as a strategic partner in fulfilling air defence equipment for the Indonesian Air Forces in the long term. The purchase of the Su-35 was Indonesia's effort to fulfil the needs of air defence equipment and modernize Indonesia's air defence agency. Keyword : Purchase  Cooperation, National Interest, Strategic Partner, Su-35